Peran Sumpah Pemuda 1928 dalam Pembentukan Bahasa Indonesia sebagai Bahasa Nasional - Qanita, Rameyza Elya; Aulia, Keisya; Azizah, Sifa Nur; Diaswari, Febi Diba; Fu'adin, Ahmad (UNIVERSITAS SERAMBI MEKKAH, 2025)
Indonesian youth realized the importance of one language to unite diverse ethnicities and cultures. In this context, they pledged the Youth Pledge in 1928, which became a commitment to make Bahasa Indonesia a national identity. To explore more deeply, this research uses a descriptive qualitative approach with data collection techniques through literature studies. The purpose of this research is to reveal the role of the Youth Pledge in the development of the Indonesian language and its impact on national unity. Thus, it is hoped that this research can provide a deeper insight into the contribution of the Youth Pledge in strengthening national identity and unity in Indonesia.